Preferences and Perspectives of Black Male Barbershop Patrons on Receiving Health Care in Nontraditional Settings (Mary Ann Liebert, 2023)
Introduction: Non-Hispanic Black men experience a disproportionate rate of morbidity and mortality from hypertension, cardiovascular disease, and other chronic conditions in the United States. Studies have demonstrated the efficacy of community-based health outreach in settings not traditionally utilized for health care. Understanding how potential future participants view health care services in nontraditional settings is a necessary step to ascertain the success of these interventions in the real world. Our study objective was to explore the preferences of Black male barbershop patrons regarding health care-provided services in these nontraditional settings. Methods: We recruited patrons of a Black-owned barbershop in the San Francisco Bay Area. Study participants were asked to complete a survey assessing individual attitudes and preferences toward the idea of receiving health care services in traditional and nontraditional settings. Results: Among non-Hispanic Black males (n=17), 81% agreed or strongly agreed that they would prefer to receive health care in traditional clinics. Receiving care at the pharmacy (56% agreed or strongly agreed) and the patient's own home (53% agreed or strongly agreed) were the next most preferred locations. A minority of participants agreed or strongly agreed that they preferred to receive health care in nontraditional settings: 47% for barbershops, 19% for churches, and 6% for grocery stores. Discussion: Participants expressed preference for traditional over nontraditional settings, despite listing barriers that may be addressed, in part, by nontraditional settings. One potential reason for this is simply a lack of familiarity. Establishing and normalizing nontraditional clinical settings may allow for enhanced acceptance within Black communities, ultimately increasing health care access.